Differences in Oral Health-Related Quality of Life (OHRQoL) by Adolescent Characteristics - Siti Fatimah; Akhmad Rifandi; Sekar Restuning (Poltekkes Kemenkes Kupang, 2023)
Adolescents are involved in one of the vulnerable groups to have dental and oral health problems, including dental caries and gum disease. If such problems are not treated well, they can interfere with the welfare of adolescents, which can further impact the overall quality of life of adolescents in everyday life. This study aims to determine differences in OHRQoL by gender, age, and grade among adoelscents at Islamic schools in Banjarmasin City. This was an analytical study with cross sectional design. A total of 170 study subjects participated in this study. The study variables were collected online via google form. The results of the Independent t-test showed that there was a difference in OHRQoL by gender (p-value of 0.016 ≤ α 0.05). On the other hand, the results of the One Way Anova test showed no difference in OHRQoL by age (p-value of 0.684 > α 0.05) and grade (p-value of 0.746 > α 0.05). In conclusion, OHRQoL by gender was found to be better in males than females. However, there was no difference in OHRQoL by age and grade. Promotive and preventive efforts need to be performed so that adolescents can improve maintenance of dental and oral health, and can manage are complaints regarding the oral cavity immediately.